2017
DOI: 10.1155/2017/7509098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Film Thickness and Heat Treatment on the Physical Properties of Mn Doped Sb2Se3 Nanocrystalline Thin Films

Abstract: Nanocrystalline thin films of Sb37.07Mn1.95Se60.98 with different thickness (7, 20, 40, and 80 nm) were successfully prepared via inert gas condensation technique. As-deposited films showed amorphous structure by grazing incident in-plane X-ray diffraction (GIIXD) technique. All films of different thicknesses were heat treated at 433 K for 90 min. The GIIXD pattern of annealed films showed nanocrystalline orthorhombic structure. The effect of thickness of annealed films on the structure and optical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This may cause by increasing spray time which also will increase the thickness of thin film. As stated by earlier researchers [26,27], crystallinity increases due to increase in deposition time (spray time) which also imply to the thickness of thin films. Thus, from the XRD analysis it can be concluded that the best film prepared is sample 4Y which has the largest crystallite size (46.30 nm) with 40 seconds spray time and 40 cm substrate to nozzle distance.…”
Section: Results and Analysis 31 Physical Characterizationmentioning
confidence: 61%
“…This may cause by increasing spray time which also will increase the thickness of thin film. As stated by earlier researchers [26,27], crystallinity increases due to increase in deposition time (spray time) which also imply to the thickness of thin films. Thus, from the XRD analysis it can be concluded that the best film prepared is sample 4Y which has the largest crystallite size (46.30 nm) with 40 seconds spray time and 40 cm substrate to nozzle distance.…”
Section: Results and Analysis 31 Physical Characterizationmentioning
confidence: 61%
“…During SSD-induced self-assembling, the smaller deposited particles of indium desorb more atoms than larger ones, which stops the growth of nanostructures from particles smaller than a certain critical radius. There are a number of studies on the influence of the degree of surface coverage of the template on the morphology of nanostructures obtained on the surface [19][20][21][22]. We were able to establish an exponential dependence of the kinetics of the increase in the periodicity of nanostructures formed on the template surface via the degree of indium deposited coverage followed by the SSD process.…”
Section: Stm Study Of Inte (001) Crystal Surface After Indium Deposition and Ssd Nanostructures Formationmentioning
confidence: 82%
“…In addition, this grain size will increase if the thickness or chemical composition increases. These two factors will directly change the material (thin film) band gap (El Zawawi et al, 2017). Therefore, even though the same material was used, the optical energy band gap would change significantly with thickness and chemical composition changes.…”
Section: Resultsmentioning
confidence: 99%